Implementation of didactic activities for teaching english speaking skills. - Analuisa Zumba, Nicole Maite; Flores Macías, Adriana María (Machala, 2022)
In the teaching of English as a foreign language, in this case the correct acquisition of speaking skills, it is of utmost importance for the learners since it allows their competent development in the teaching-learning process. The current research work was carried out with the purpose of improving the learning of speaking skills in English. By implementing a didactic activities system based on active learning methods after evidencing the absence of didactic activities in class. The research responds to a qualitative paradigm with a descriptive design in which the use of a didactic activities system based on active learning methods for the improvement in English-speaking skills is analyzed. For the theoretical framework construction, the bibliographical documentation was used to support the validity and reliability of the research. Additionally, with the help of empirical methods such as participant observation, diagnostic test, and teacher interview, it was possible to diagnose the initial state of the population under study made up of first level “H” students from Centro de Educación Continua de la Universidad Técnica de Machala leaving aside the selection of the sample. Thus, considering the existing student’s needs, a didactic activities system based on active learning methods is proposed for the achievement of meaningful learning of the pupils. Finally, it is suggested to continue researching the topic using a variety of innovative activities aligned to constructivism, in order to fulfill the communicative competence, aim in speaking skills.
En la enseñanza del inglés como lengua extranjera, en este caso la correcta adquisición de la habilidad de la expresión oral, es de suma importancia ya que permite el desenvolvimiento competente de los estudiantes en el proceso de enseñanza aprendizaje. El presente trabajo de investigación se realizó con el fin de mejorar la expresión oral en inglés por medio de la implementación de un sistema de actividades didácticas de métodos activos luego de evidenciar las falencias presentadas en los estudiantes. La investigación responde a un paradigma cualitativo con un diseño descriptivo en el que se analiza el uso del sistema de actividades didácticas de métodos activos para el mejoramiento de la expresión oral en inglés. Para la construcción de marco teórico se recurrió a la documentación bibliográfica la misma que fundamenta la validez y fiabilidad de la investigación. Adicionalmente, con la ayuda de los métodos empíricos como la observación participante, test de diagnóstico, y entrevista al docente, permitieron diagnosticar el estado inicial de la población en estudio conformado por los estudiantes de primer nivel del paralelo “H” del Centro de Educación Continua de la Universidad Técnica de Machala dejando de lado la selección de la muestra. Es así que considerando las necesidades existentes en el alumnado se aporta con un sistema de actividades didácticas de métodos activos, para el aprendizaje significativo de los estudiantes. Finalmente se sugiere seguir abordando el tema haciendo uso de diferentes actividades innovativas alineadas al constructivismo, para así cumplir con el objetivo de la competencia comunicativa en estudio.
Keywords: SPEAKING SKILLS; SYSTEM; DIDACTIC ACTIVITIES; ACTIVE LEARNING